Work requirements, expenditures, and labor supply decisions: Evidence from Malawi - Ambler, Kate; Godlonton, Susan (International Food Policy Research Institute, 2019)
A major goal of social protection programs run by governments and NGOs in the developing world is to provide income support to individual and households living in poverty. These programs tend to be split between cash transfer programs that provide cash to families with no conditions, and public works programs that require participants to work in order to receive the cash payments. Despite the widespread nature of both types of programs, and large literatures that examine their impacts, there exists little work directly comparing them. Such a comparison would be useful to policy makers considering whether a cash transfer or public works program better meets their goals.